DEMOGRAPHIC FACTORS AND PARENTS’ COMMUNICATIVE ACTS: THEIR IMPLICATIONS ON MODELS OF CHILD’S USE OF LANGUAGE - Rafael Ibe Santos (International Journal of Humanity Studies (IJHS), 2022)
This case study investigated Halliday’s models of child’s use of language involving an English-Filipino bilingual boy and how he was influenced by certain demographic factors and parents’ communicative acts. Data was from nine videos that captured the child’s naturally occurring interactions involving his parents and family friends between the ages 2.6 and 4.10 within a span of almost three years. The multimethod approach was used in analyzing data, namely, qualitative frequency analysis and online interview for triangulation purposes. Five of the seven functions of language in children were demonstrated and appeared to have been influenced by ethnicity, age, gender, and parents’ communicative acts and attitude but not by bilingualism as earlier predicted. More importantly, four nascent models were exhibited, suggesting that there could be more than seven language functions in children as previously posited by Halliday. The esteem function, rescue function, corrective function, and asserting function, reflective of models of child’s use of language in Filipino and Asian contexts, were discovered and such typologies are proposed in this study. Findings have implications on bilingualism, language teaching, and language development theories.